Development of the "Learning Factory" Model and Concept For Vocational Education (Pengembangan Model Dan Konsep “Learning Factory” Untuk Pendidikan Vokasi) - Rudiyanto, San (Journal of Innovation and Applied Technology, 2024)
Learning Factory is a promising method for building competency through education, training and research activities, including vocational education, which requires students to achieve applied skills. This research aims to develop a concept/model for curriculum integration of existing study programs in vocational education with industrial partners through a learning factory approach. This type of research uses a descriptive qualitative approach, with data sources obtained from observation, interviews, Focus Group Discussions (FGD), and reference sources from literature, books about learning methods and scientific research results on relevant topics. The targeted output of the research is the "Vocafe" Learning Factory learning integration model which will later be used as a guideline in operating the "Vocafe" laboratory as a learning factory for students at the Vocational Faculty of Brawijaya University.